2022
DOI: 10.3233/ies-210155
|View full text |Cite
|
Sign up to set email alerts
|

The effect of active vs passive recovery and use of compression garments following a single bout of muscle-damaging exercise

Abstract: BACKGROUND: Some recovery strategies are needed to reduce or eliminate the effect of negative symptoms caused by exercise. OBJECTIVE: The aim of this study was to determine the effect of different types of recovery after single-bout strength exercises on biomarkers of muscle damage, cytokine release and lactate elimination. METHODS: Following familiarization, 10 male volunteers performed four randomized recovery protocols (passive or active recovery with or without compression garments) following a single bout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A variety of measures have been used to ascertain the influence of CGs on recovery at a physiological level, predominantly concerned with blood concentrations of muscle proteins or metabolites. There appears to be a trend for reduced blood/plasma concentrations of lactate dehydrogenase, with significant reductions following 60-80 min of recovery with CGs after submaximal [120] and maximal [11] cycling, as well as upper body [136] and lower body [137] resistance exercise protocols, compared to control groups. As well, wholebody garments were associated with a significant reduction in blood lactate following a whole-body resistance workout [127] and a small reduction in blood lactate 24 h following a competitive trail race [138].…”
Section: Physiological Effects During Recoverymentioning
confidence: 88%
See 2 more Smart Citations
“…A variety of measures have been used to ascertain the influence of CGs on recovery at a physiological level, predominantly concerned with blood concentrations of muscle proteins or metabolites. There appears to be a trend for reduced blood/plasma concentrations of lactate dehydrogenase, with significant reductions following 60-80 min of recovery with CGs after submaximal [120] and maximal [11] cycling, as well as upper body [136] and lower body [137] resistance exercise protocols, compared to control groups. As well, wholebody garments were associated with a significant reduction in blood lactate following a whole-body resistance workout [127] and a small reduction in blood lactate 24 h following a competitive trail race [138].…”
Section: Physiological Effects During Recoverymentioning
confidence: 88%
“…Similarly, the majority of investigations did not find any change in measures of creatine kinase [12,13,128,131,133,139,[141][142][143][144], though clearly, there was substantial variation in the type of exercise protocols used, which makes it difficult to establish the relevance of CK as an index of muscle damage in the first instance. With this in mind, the studies that reported significant reductions in CK with the use of CGs tended to implement explosive, eccentric-focused exercise modalities, e.g., repeat sprint and drop jump protocols [121,123,127,130,134,145] and heavy resistance exercise [137], which are known to elicit greater levels of muscle damage than endurance and non-load bearing exercise [146]. Inflammatory cytokines such as plasma IL-6, tumour necrosis factor alpha, and C-reactive protein are also commonly measured to establish the influence of CGs on systemic inflammation and tissue damage; however, studies have generally not reported any significant effect of the garments on these measures [125,128,129,133,134,[137][138][139][140][141]144].…”
Section: Physiological Effects During Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐four studies, including 64 intervention groups with a total of 495 participants (89% male/11% female), were included in this systematic review and meta‐analysis. From the total of 34 studies included in the meta‐analyses, 29 studies investigated IL‐6 with 56 effect sizes, 55,74‐100 11 examined IL‐10 with 24 effect sizes, 55,74,75,77‐80,85,88,89,97 and further 5 analyzed IL‐1ra with 14 effect sizes 77,83‐85,97 . Nine studies with 15 effect sizes looked into TNF‐α, 75,78,87,89,96,98,101‐103 and five studies accounting for eight effect sizes investigated IL‐15 33,88,91,104,105 .…”
Section: Resultsmentioning
confidence: 99%
“…From the total of 34 studies included in the meta‐analyses, 29 studies investigated IL‐6 with 56 effect sizes, 55,74‐100 11 examined IL‐10 with 24 effect sizes, 55,74,75,77‐80,85,88,89,97 and further 5 analyzed IL‐1ra with 14 effect sizes 77,83‐85,97 . Nine studies with 15 effect sizes looked into TNF‐α, 75,78,87,89,96,98,101‐103 and five studies accounting for eight effect sizes investigated IL‐15 33,88,91,104,105 . As displayed in Table 2, only two studies investigated the effects of resistance exercise on female participants, 88,97 and two studies had at least one female intervention group investing sex‐dependent differences in results 74,99 .…”
Section: Resultsmentioning
confidence: 99%